2018
DOI: 10.2135/cropsci2018.02.0116
|View full text |Cite
|
Sign up to set email alerts
|

Growth‐Stage‐Based Irrigation Management on Biomass, Yield, and Yield Attributes of Spring Canola in the Southern Great Plains

Abstract: 2623 RESEARCHL imited water availability is one of the major constraints to agricultural production in the semiarid US Southern Great Plains (SGP). Erratic rainfall and frequent droughts further aggravate stress on agriculture in the region (McGuire, 2012). The Ogallala aquifer is the main resource for irrigation in SGP (Chaudhuri and Ale, 2014). Excessive use of groundwater for irrigation has significantly depleted the aquifer. A recent study showed that the aquifer lost 31 and 33% of its water storage in New… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 45 publications
(92 reference statements)
0
3
0
Order By: Relevance
“…Confusion among farmers to identify the specific cause of crop damage either due to biotic stress (insects, plant diseases and weeds) or abiotic stress particularly drought resulted false perception among farmers that increasing pesticide dose improve crop production. Integrated pesticide management strategies with minimal chemical pesticide dose along with growth stage-based irrigation would be a better fit for low input farming conditions (Katuwal et al, 2018). Table 3.…”
mentioning
confidence: 99%
“…Confusion among farmers to identify the specific cause of crop damage either due to biotic stress (insects, plant diseases and weeds) or abiotic stress particularly drought resulted false perception among farmers that increasing pesticide dose improve crop production. Integrated pesticide management strategies with minimal chemical pesticide dose along with growth stage-based irrigation would be a better fit for low input farming conditions (Katuwal et al, 2018). Table 3.…”
mentioning
confidence: 99%
“…Similar results of all growth parameters were reported by Sharma (2009) [10] and Ardestani et al (2011) [3] . Katuwal et al (2018) [6] also found that irrigation at flowering stage increases the LAI.…”
Section: Leaf Area Index (Lai)mentioning
confidence: 94%
“…These results confirm that a satisfactory supply of water at the reproductive stage of canola is key for improved WUE. As the overall aboveground biomass and leaf area index reach a peak during the reproductive stage (Katuwal et al 2018), it likely increases total water loss through surface transpiration and increases ET in canola. In addition to the increased ET requirement, the reproductive stage is characterized by many water-sensitive processes such as floral retention, floral bud development into pods and assimilate supply from leaves and pods for seed setting which determines yield in oilseed crops (Eck et al 1987;Sweeney et al 2003;Katuwal et al 2020).…”
Section: Improving Wue Of Canolamentioning
confidence: 99%